Evaluation of Multiple Methods for Quantification of Glycosaminoglycan Biomarkers in Newborn Dried Blood Spots from Patients with Severe and Attenuated Mucopolysaccharidosis-I - Zackary M. Herbst; Leslie Urdaneta; Terri Klein; Maria Fuller; Michael H. Gelb (MDPI AG, 2020)
All newborn screening (NBS) for mucopolysaccharidosis-I (MPS-I) is carried out by the measurement of α-iduronidase (IDUA) enzymatic activity in dried blood spots (DBS). The majority of low enzyme results are due to pseudodeficiencies, and studies from the Mayo Clinic have shown that the false positive rate can be greatly reduced by including a second-tier analysis of glycosaminoglycans (GAGs) in DBS as part of NBS. In the present study, we obtained newborn DBS from 13 patients with severe MPS-I and 2 with attenuated phenotypes. These samples were submitted to four different GAG mass spectrometry analyses in a comparative study: (1) internal disaccharide; (2) endogenous disaccharide; (3) Sensi-Pro; (4) Sensi-Pro Lite (a variation of Sensi-Pro with a simplified workflow). Patients with attenuated MPS-I show less GAG elevation than those with severe disease, and all MPS-I patients were separated from the reference range using all four methods. The minimal differential factor (lowest GAG marker level in MPS-I samples divided by highest level in the reference range of 30 random newborns) was about two for internal disaccharide, Sensi-Pro, and Sensi-Pro Lite methods. The endogenous disaccharide was clearly the best method with a minimal differential of 16-fold. This study supports use of second-tier GAG analysis of newborn DBS, especially the endogenous disaccharide method, as part of NBS to reduce the false positive rate.